2021
DOI: 10.3310/hta25460
|View full text |Cite
|
Sign up to set email alerts
|

Home environmental assessments and modification delivered by occupational therapists to reduce falls in people aged 65 years and over: the OTIS RCT

Abstract: Background Falls and fall-related fractures are highly prevalent among older people and are a major contributor to morbidity and costs to individuals and society. Only one small pilot trial has evaluated the effectiveness of a home hazard assessment and environmental modification in the UK. This trial reported a reduction in falls as a secondary outcome, and no economic evaluation was undertaken. Therefore, the results need to be confirmed and a cost-effectiveness analysis needs to be underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 72 publications
0
6
0
3
Order By: Relevance
“…Four models evaluated single-component models, where environmental modification was the only aging-in-place intervention. Of these interventions, one trial showed positive outcomes (Nikolaus & Bach, 2003), two demonstrated mixed negative outcomes (Pardessus et al, 2002; Pighills et al, 2011), and one produced negative outcomes (Cockayne et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four models evaluated single-component models, where environmental modification was the only aging-in-place intervention. Of these interventions, one trial showed positive outcomes (Nikolaus & Bach, 2003), two demonstrated mixed negative outcomes (Pardessus et al, 2002; Pighills et al, 2011), and one produced negative outcomes (Cockayne et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The OT-led intervention group saw a significant reduction in the number of falls compared to control ( p = 0.005), but no effect was seen in fear of falling ( p = 0.90), quality of life ( p = 0.38), or ADL independence at 12 months ( p = 0.87). Cockayne et al (2021) conducted the OTIS RCT in England from October 2016 to April 2018. Similar to Pighills et al, a singular home visit was conducted by the OT with 4–6-week telephone follow-up using the Westmead home safety assessment to identify fall-related hazards, review strategies to mitigate fall-risks, and make recommendations on changes to the home environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…У процесі старіння людини поступово накопичується кількість захворювань, особливо хронічних, з'являються хвороби, асоційовані із віком (зокрема, нейродегенеративні), знижуються можливості адаптації до екзогенних та ендогенних впливів. Відповідно, захворюваність у віковій категорії 60-74 роки у 2 рази вища, у віці 75 років і старше -у 6 разів вища, ніж у осіб молодого віку [2,3].…”
Section: ефективність корекції фізичного статусу хворих з коморбідніс...unclassified